The Transcription Factor VpxlnR Is Required for the Growth, Development, and Virulence of the Fungal Pathogen Valsa pyri - He, Feng; Kange, Alex-Machio; Yang, Jie; Xiao, Jiaxin; Wang, Rongbo; Yang, Lu; Jia, Yifan; Fu, Zheng Qing; Zhao, Yancun; Liu, Fengquan (Frontiers in Microbiology, 2022)
Pears (Pyrus sp.) are widely cultivated in China, and their yield accounts for more than 60% of global pear production. The fungal pathogen Valsa pyri is a major causal agent of pear canker disease, which results in enormous losses of pear production in northern China. In this study, we characterized a Zn2Cys6 transcription factor that contains one GAL4 domain and a fungal-trans domain, which are present in VpxlnR. The vpxlnR gene expression was upregulated in the invasion stage of V. pyri. To investigate its functions, we constructed gene deletion mutants and complementary strains. We observed that the growth of the vpxlnR mutants was reduced on potato dextrose agar (PDA), Czapek plus glucose or sucrose compared with that of the wild-type strain. Additionally, vpxlnR mutants exhibited loss of function in fruiting body formation. Moreover, vpxlnR mutants were more susceptible to hydrogen peroxide (H2O2) and salicylic acid (SA) and were reduced in their virulence at the early infection stage. According to a previous study, VpxlnR-interacting motifs containing NRHKGNCCGM were searched in the V. pyri genome， and we obtained 354 target genes, of which 148 genes had COG terms. PHI-BLAST was used to identify virulence-related genes, and we found 28 hits. Furthermore, eight genes from the 28 PHI-BLAST hits were further assessed by yeast one-hybrid (Y1H) assays, and five target genes, salicylate hydroxylase (VP1G_09520), serine/threonine-protein kinase (VP1G_03128), alpha-xylosidase (VP1G_06369), G-protein beta subunit (VP1G_02856) and acid phosphatase (VP1G_03782), could interact with VpxlnR in vivo. Their transcript levels were reduced in one or two vpxlnR mutants. Taken together, these findings imply that VpxlnR is a key regulator of growth, development, stress, and virulence through controlling genes involved in signalling pathways and extracellular enzyme activities in V. pyri. The motifs interacting with VpxlnR also provide new insights into the molecular mechanism of xlnR proteins.